Beneficial Effect of Immune-Enhanced Enteral Nutrition on Immune Function in Patients With Severe Neurological Diseases: A Single-Center Randomized Controlled Trial - Chao, Ke; Wang, Dong; Yang, Hongfu; Ma, Ning; Liu, Qilong; Sun, Xiaoge; Sun, Rongqing (Frontiers in Nutrition, 2021)
Background: Undernutrition is the main reason for the use of artificial nutrition in patients with severe neurological diseases. However, the clinical and immunological outcomes of enteral nutrition supplemented with immunomodulatory nutrients in these patients remain unclear. Methods: In this single-center, randomized controlled study, 57 patients with severe neurological diseases were randomly divided into the following two groups according to the type of enteral nutrition they would receive: immune-enhancing (IE) (n=27) and non-IE (NIE) (n=30). The IE and NIE groups received enteral nutrition supplemented with immunomodulatory nutrients and standard enteral nutrition, respectively. We compared the nutritional status and the state of cellular immunity between the patients of the two groups. Clinical and immunological variables were evaluated following nutritional treatment. Results: Feeding intolerance was lower in the IE than that in the NIE group (P = 0.04). However, there were no significant differences between the results of the two groups in terms of length of stay in the intensive care unit or hospital, extubation time, or body mass index (P > 0.05). The CD4+ T-lymphocyte count and CD4+/CD8+ ratio in the peripheral blood increased significantly in the IE group. The expression of CD28 activated cell surface markers was higher in the IE than in the NIE group. In addition, increased plasma interferon-γ levels were recorded in the IE group, whereas the levels of tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-8, and IL-10 decreased. Conclusions: Immune-enhanced enteral nutrition could improve the immune status and feeding tolerance in patients with severe neurological diseases.